PROBLEMS OF REPRODUCTION OF HUMAN RESOURCES TOWARDS THE FORMATION OF THE DIGITAL ECONOMY - Vertakova, Yulia Vladimirovna; Charochkina, Ekaterina Yurievna; Leontyev, Evgeniy Dmitrievich (Journal of Applied Engineering Science, 2019)
The article is devoted to the problems of reproduction of human resources as the basis of the digital economy. The factors and conditions of formation of human resources in the digital economy are determined. It is established that the existing human potential is implemented inefficiently, which hinders the development of knowledge-intensive industries, the expansion of the scientific potential of the country. Such trends are very dangerous and can spread widely and cause great damage to society and the economy. The reform of the scientific and educational sphere in the context of the development of the information society is necessary, and the most effective in this direction are public investments in the diversification of production and training of the population, the close connection of production with innovation, science and education. Today it is important not only to solve the problems of reproduction of human resources, but also the problems of formation of a new factor of production for the development of digital society.
Keywords: reproduction; products; humans; digitization